Don't hold back : let's talk organ donation - Ee, Xue Jing (Nanyang Technological University, 2021)
Don’t Hold Back is a communication campaign that encourages young adults aged 21 to 29 to initiate conversations on deceased organ donation with their families. Although all Singaporeans and Permanent Residents are deemed deceased organ donors under the Human Organ Transplant Act (HOTA) upon turning 21, many are unfamiliar with it and raise objections to the retrieval of organs for their deceased family members. The campaign addresses the issue by creating more conversations within families so that there is clarity and certainty over the deceased’s wishes when organ donation is brought up, therefore reducing the emotional stress faced by family members acting as proxy-decision makers. With more conversations, a ripple effect on enhancing the quality of Singapore’s organ donor pool may be achieved. The fully digital campaign ran from December 2020 to March 2021 and successfully increased the number of conversations on deceased organ donation by 4.8%, intention to do so by 33.9%, and perceived relevance of the issue by 10.2%. Based on the Theory of Planned Behaviour and formative research to understand our target audience, we developed an effective strategy using triggers to create opportunities for such conversations to arise in families. These triggers include engaging videos, relatable comic strips and human interest stories that act as cues to action. This paper details the campaign process from conception to conclusion, and recommendations to guide further campaigns and studies on increasing deceased organ donation rates in Singapore.